New records and a new species of the cavernicolous genus Guiodytes Tian, 2013 from Guangxi, China (Coleoptera: Carabidae: Scaritinae) - Tian, Mingyi (Zootaxa, 2014)
A new species of the genus Guiodytes Tian, 2013 is described from a limestone cave called Shuiku Dong in Huanjiang County of northernmost Guangxi, southern China. G. deharvengi n. sp. is the first depigmented species of Guiodytes. It is close to G. cavicola Tian, 2013, but easily recognized by its broader and yellowish brown body. In addition, new records for G. cavicola Tian, 2013 are provided from two caves in Du’an County of northern Guangxi, with description of the male genitalia. A key to all three known species and a distributional map of Guiodytes are also given.